To wait for a spontaneous recovery of the third cranial nerve palsy occurring after the coiling of a PComA aneurysm or to implement surgical treatment? – A case report - Peulić, Miodrag; Kovačević, Vojin Stevo; Miletić Kovačević, Marina; Grujičić, Danica (Vojnosanitetski pregled, 2018)
Introduction. In the last two decades a method of endovascular embolization has been imposed as a method of choice in the treatment of unruptured intracranial aneurysms. Therefore, the problem of treating posterior communicating artery (PComA) aneurysms presenting with the third cranial nerve (TCN) palsy has become even more complex. The case of a patient reported in the paper itself has presented a dilemma of whether to wait for spontaneous resolution of ophthalmoplegia developed after the coiling of a PComA aneurysm or whether to implement an early surgical treatment. Case report. An unruptured saccular aneurysm, directed inferolaterally in the right internal carotid artery (ICA) segment in the position of the PcomA origin, was diagnosed in a 58-year-old male patient. The aneurysm was measuring 9 mm in diameter while the neck was measuring 5 mm. The day before the planned embolization, the patient developed ipsilateral ophthalmoparesis, whereas the first day after the endovascular procedure was completed, the patient developed right-sided complete ophthalmoplegia. Ten weeks after the endovascular embolization our team decided to perform a microsurgical treatment including aneurysm clipping and coil extraction. Eighteen months after the surgery, the patient made a full recovery of the functions of musculus (m) levator palpabrae, m. rectus medialis and pupillary function, with a partial recovery of the functions of m. obliqus inferior, m. rectus inferior and m. rectus superior. Conclusion. According to medical research and literature, the partial recovery of the TCN palsy is expected to happen in the first few weeks after embolization. Despite the completion of endovascular treatment progression of ophthalmoparesis to ophthalmoplegia without any simptoms of clinical improvement after 10 weeks is considered to be an indicator of long-standing TCN compression, which can lead to irreversible nerve damage. Despite the increase in the use of an endovascular embolization method in the treatment of PComA aneurysms preceeded by the TCN palsy, neurosurgical treatment is believed to have been necessary. Still, there is one question left to be answered - did we react too late in this particular case?
Keywords: intracranial aneursym; oculomotor nerve; embolization; therapeutic; neurosurgical procedures; ophthalmoplegia; recovery of function